(untitled) (Journal of Legal Studies, 2020)
The development of informative technologies, including that of the Internet, has significantly changed the human’s life. The largest portion of civil turnover has been encompassed by e-commerce. This latter is being executed through e-contracts. The econtract from the doctrinal point of view is considered as dealt and the existence of esignature is an essential component of its authentication, which in its turn determines the issue of existence-absence of written form. The present article is related to the issues of legal status, technical safety and reliable environment of application of e-signature. The necessity of applying the legal instrument was conditioned by the necessity of gradual disappearance of paper-based operations’ execution practice. The application of e-document turnover is justified only in case if the authentication of the document and the signature placed on it has been followed and all this has been acknowledged by the third party. Despite the various models of e-signature, for all of them, it is important to have a reliable and safe environment, for guaranteeing the safety and signer’s identity. The article shows the issues related to legal governing of e-signature according to the legislation of Georgia, also Russian Federation, Continental Europe, Common Court member states, as well as directives and guidelines developed by international organizations.